“Thousands of Vendings”: Languages in Contact in a Danish Television Show - Nielsen, Jean (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
The North American inclination towards monolingualism is far from the norm, as exemplified by the acceptance of multilingualism in nations such as Denmark, where linguistic pluralism is valued for the versatility it brings to linguistic expression and style. The Danish mini-series “The Julekalendar” is a case study for the kind of language mix embraced and enjoyed by a linguistically sophisticated population. Its uniqueness lies in the linguistic assumptions it makes of its audience by mixing languages, dialects, and language play in the delivery of content, without the aid of subtitles. “The Julekalendar” shows the admirable confidence of the Danish people in their language and its ability to withstand - or incorporate sucessfully - the influences of other languages.